RELATIONSHIP BETWEEN STRESS LEVEL AND FATIGUE AMONG NURSING STUDENT AT LAMBUNG MANGKURAT UNIVERSITY - Noor, Fitriati; Rahmah, Mutia; Septiany, Maulidya (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Introduction : Stress is a feeling of pressure on a person due to demands from various things such as the environment around the individual, physical conditions, and social situations that cannot be controlled. One of the negative impacts of stress is fatigue which can interfere with daily activities in nursing students. Aim : This study was to determine the relationship between stress levels and fatigue in nursing students at Lambung Mangkurat University. Metode : This study used a cross sectional design. The technique used is stratified random sampling. The research sample amounted to 80 Lambung Mangkurat University Nursing Students. Data collection using a questionnaire. The analysis test used the Spearman correlation test. Results : The level of stress experienced by nursing students at Lambung Mangkurat University is the majority of moderate stress with a total of 62 people (77.5%) and fatigue experienced by students is the majority of significant fatigue, namely 70 people (87.5%). There is a positive and strong relationship between stress levels and fatigue in nursing students at Lambung Mangkurat University (p-value 0.000